A Research on Estimation of Emotion Using EEG Signals and Brain Computer Interfaces - Yildirim, Nilay; Varol, Asaf (Ieee, 2017)
The brain produces weak electrical signals that can be measured from the skull. Electroencephalography (EEG) is a method that provides monitoring electrical activity of the brain with the electrical methods. Brain Computer Interface (BCI) is a system that converts the electrical signals produced by the brain to the signals that can be interpreted by a computer or an electronic system. Brain Computer Interface aims to produce the result on developed computer systems rather than creating a response in the body from the signals sent by the brain. Emotion is defined as a psychophysiological change in the mood of a person that emerges by interaction with biochemical and environmental effects. There are many methods on emotion recognition research. These include voice recognition, recognition with mimics, and so on. However, face expression or tone of voice does not always represent feelings. Skin conductivity, skin temperature changes, blood pressure, heartbeat are also used for emotion estimation. In addition, BCI research on emotional recognition is important in recent years and it's still a new topic in research. In this paper, studies on emotion estimation using EEG signals and the brain computer interface studies in this subject have been examined and the lack of relevant literature on this subject are discussed.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: electroencephalography; emotion recognition; brain computer interface